Restoring the species status of Catharus maculatus (Aves: Turdidae), a secretive Andean thrush, with a critique of the yardstick approach to species delimitation - Halley, Matthew R.; Klicka, John C.; Clee, Paul R. Sesink; Weckstein, Jason D. (Zootaxa, 2017)
In the 1850s, two species of "Spotted" Nightingale-Thrush (Aves: Catharus) were independently described from montane rainforests of Guatemala, C. dryas (Gould, 1855) and Ecuador, C. maculatus (Sclater, 1858). However, due to similarities in plumage color, C. maculatus was reclassified as a subspecies of C. dryas in 1878, a decision that has been upheld for 137 years. We collected multiple lines of evidence including phylogenetic analysis of mitochondrial DNA sequences (ND2), discriminant and principal components analysis of morphometric and vocal data, and statistical modeling of ecological niches, that collectively indicate that C. d. dryas and C. d. maculatus are independent species. We recommend restoring species status to C. maculatus of South America and applying the common name Sclater’s Nightingale-Thrush to this species.